Return-to-play for elite athletes with genetic heart diseases predisposing to sudden cardiac death - Martinez, K. A.; Bos, J. M.; Baggish, A. L.; Phelan, D. M.; Tobert, K. E.; Newman, D. B.; Scherer, E.; Petek, B. J.; Ackerman, M. J.; Martinez, M. W. (Journal of the American College of Cardiology, 2023)
Background People diagnosed with genetic heart diseases (GHDs) associated with sudden cardiac death (SCD) have historically been restricted from competitive sports. Recent data documenting return-to-play (RTP) experiences following shared decision making (SDM) suggest that cardiac event rates for athletes with a GHD are lower than previously described, thereby suggesting an opportunity to reconsider this paradigm.